Local Wisdom Based Tourism Branding Efforts on the Site of Orang Kayo Hitam Jambi - Noor Khalida Magfirah; Muhaimin Muhaimin (Jurnal Komunikasi, 2023)
Orang Kayo Hitam is a Malay King of Jambi with historical relics located in Simpang Village, Berbak District, East Tanjung Jabung Regency, Jambi. His name is well known in Jambi, but his legacy is not yet known by the wider population. The local government designated this cultural heritage as a Regional Tourism Strategic Area (KSPD). This study aims to discuss the tourism potential of transforming the Orang Kayo site, which is full of local wisdom values, into a distinctive tourist destination brand. This research uses a natural approach and qualitative methods, including life stories, interviews, observations, interactions, historical and visual texts, and natural approaches. The findings show that local knowledge about the rituals of the community around the location, especially the Haul of Datuk Orang Kayo Hitam, is an attraction for tourists. At the government level, efforts to develop tourist area infrastructure continue to be made to develop the tourism potential of the Orang Kayo Hitam Site. In branding efforts, there is no specific branding to make this area a tourist destination. Online media, for example, has not been utilized properly as a means of publication and promotion. Local wisdom and unique cultural values at the Orang Kayo Hitam site. Strategic tourism areas require special attention in order to attract tourists. Tourism attraction can be obtained by exploring tourism potential in a bottom-up manner in an effort to find the uniqueness of local wisdom tourism potential. Of course, this process requires communication between the stakeholders involved